TECHNIQUES OF STORAGE STAPHYLOCOCCUS AUREUS ON CELL VIABILITY AS A REFERENCE FOR ISOLATE PRESERVATION IN MICROBIOLOGY LABORATORIES - Yannuarsita, Deni; Sasmito, Moch Shandy; Riyadi, Eko Slamet; Hilmi, Mustofa (Universitas Muara Bungo, 2025)
Preservation of isolates is carried out as an effort to collect and conserve microbial germplasm and to ensure its availability for future research and applications. The purpose of this research to evaluated the effectivity of temperature (5ºC and -4ºC) during 84 days to prevent viability of staphylococcus aureus, which can be used as a model inactivation kinetic and recommendation determine in the microbiology laboratorium. The research was conducted at the Microbiology Laboratory of the Agricultural Department, Banyuwangi State Polytechnic, from June to September 2025. The temperature are 5°C and –4°C, and the period are 0, 14, 28, 42, 56, 70 and 84 days. All test isolates were suspended in Tryptone Soy Broth (TSB) and supplemented with 15 % glycerol. Analysis of variance revealed a highly significant interaction (P 0.001) between temperature and storage period on Staphylococcus aureus viability. At 5 °C, colony bacteria decrease from days 14 until days 80 is 0.95 log CFU/mL. At –4 °C the population of colony bacteria dropped by approximately 1.7 log CFU/mL. The study concludes that, Short-term preservation can be achieved at 5 °C, with sub-culturing recommended at weeks 4–6, Medium-term preservation at –4 °C allows sub-culturing after month 6, Long-term preservation at –4 °C is feasible, with sub-culturing possible after month 12.